International Criminal Responsibility Rising From the Ethnic Cleansing - Salem Algehiche; Raqeeb Jassim (الرافدین للحقوق, 2023)
Acts of ethnic cleansing are among the most serious and heinous crimes because they include crimes of genocide, crimes against humanity, and war crimes to achieve their goal, which is to make an area ethnically homogeneous, as they consist of committing murders, genocide, torture, rape, displacement, confiscation of property, appropriation, threats, and other crimes. Which violate human rights, against a specific group that is racially or ethnically different from the group carrying out purification in a particular region to make that region ethnically homogeneous, and despite the ugliness of these acts, international criminal law did not provide for their criminalization, which prompted some to classify them as the three international crimes. While others refused to consider it a crime, as the term ethnic cleansing is a newly created term whose features have not yet been fully clarified and its precise legal adaptation has not been agreed upon, and it has also sparked great controversy among jurists of international law and has also sparked wide disagreement on many occasions. It was exposed to by the international judiciary, where some consider it synonymous with the term genocide, while others see it as an independent crime in itself.